Peningkatan Hasil Belajar Matematika Menggunakan Model Pembelajaran Problem Based Learning (PBL) - Rokhayah, Siti (Jurnal Pendidikan Madrasah, 2024)
This study aims to improve Mathematics learning outcomes using the Problem Based Learning (PBL) learning model. This research is classroom action research with the research subject of grade VIII-B MTs Negeri 3 Bantul students. Research is carried out in 2 cycles and each cycle consists of 2 meetings, covering 4 stages, namely planning, implementation, observation and reflection. Data collection of learning outcomes is obtained by end-of-cycle tests and processed quantitatively. The results showed that there was an increase in mathematics learning outcomes of grade VIII-B MTs Negeri 3 Bantul students on the "Opportunities" material. This is shown by a significant increase in student learning outcomes which reached an average score of 65 in cycle I and 74.19 in cycle II with learning completeness of 61% in cycle I and 80.6% in cycle II, an increase of 19.6%. Learning using PBL can be used as a reference in mathematics classes in the future.